2022
DOI: 10.1002/mp.15558
|View full text |Cite
|
Sign up to set email alerts
|

Phantom task‐based image quality assessment of three generations of rapid kV‐switching dual‐energy CT systems on virtual monoenergetic images

Abstract: Purpose To compare the spectral performance of three rapid kV switching dual‐energy CT (DECT) systems on virtual monoenergetic images (VMIs) at low‐energy levels on abdominal imaging. Methods A multi‐energy phantom was scanned on three DECT systems equipped with three different gemstone spectral imaging (GSI) platforms: GSI (1st generation, GSI‐1st), GSI‐Pro (2nd generation, GSI‐2nd ), and GSI‐Xtream (3rd generation, GSI‐3rd). Acquisitions on the phantom were performed with a CTDIvol close to 11mGy. For all pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 32 publications
1
15
1
Order By: Relevance
“…The mean relative differences (±SDs) between two values were computed for the five dose levels following the same methodology previously published 36 . This allows comparison of the results obtained for each metric between two reconstruction algorithms for all dose levels.…”
Section: Methodsmentioning
confidence: 99%
“…The mean relative differences (±SDs) between two values were computed for the five dose levels following the same methodology previously published 36 . This allows comparison of the results obtained for each metric between two reconstruction algorithms for all dose levels.…”
Section: Methodsmentioning
confidence: 99%
“…In an unblinded comparison of images at similar noise magnitude, we confirmed that the DLR images with DE appeared less natural than the DLR images with SE mode. Greffier et al 24 . did not include SE mode measurements so we cannot readily compare this finding to previous results.…”
Section: Discussionmentioning
confidence: 59%
“…To our knowledge, only one group, Greffier et al, 24 have performed similar phantom evaluations for DE imaging and the TF algorithm. Overall, there is good agreement between our findings, with the main difference being larger relative improvements in noise and d' for Greffier 24 and less improvement in d' with decreased keV, possibly due to their larger phantom size. 30 Greffier et al 24 presented approximately (−56%, −8%, −7%, −95%) for (noise, f av , f 50 , d') for DE-70 keV and TF-M (relative to AR0%).…”
Section: F I G U R Ementioning
confidence: 99%
See 1 more Smart Citation
“…In addition, deep learning (DL) image reconstruction algorithms were recently developed for conventional SECT [27][28][29][30] and more recently also for DECT platforms [26,31,32]. For the Canon Medical DECT platforms, a DL-based spectral reconstruction (DLSR) is available, based on the creation of deep learning views generated by the trained neural network for opposite and for the same energy views [31,33].…”
Section: Introductionmentioning
confidence: 99%